Management and Business Sustainability Strategies for Prepaid Airtime Retail MSMEs in Maumere - Damianus Viktor Raja; Elisabeth Febianty; Leontiana Dama Veny; Bernadetha Susanti; Gonzelini Yuniani Tia (Yayasan Cerdas Pedia Indonesia, 2026)
This research investigates management and sustainability strategies of credit counter MSMEs in Maumere, Sikka Regency, amid digital disruption. Utilizing a qualitative descriptive method with a case study approach, data were gathered through triangulation involving in-depth interviews, observation, and documentation. Findings indicate that sustainability is integratively driven by human capital, specifically the owner's technical informatics background, which facilitates specialized repair services and operational efficiency. Furthermore, implementing the SERVQUAL model fosters customer loyalty, while strategic location selection optimizes daily market demand. Risk management is executed through income diversification, including hardware repairs and accessory sales, providing financial resilience against market fluctuations. These micro-level strategies significantly contribute to regional economic stability, particularly as stabilizers for Sikka's Gross Regional Domestic Product (GRDP). However, structural challenges regarding formalization via the OSS-RBA system and digital literacy persist. Consequently, synergy between human capital investment and technological adaptation remains vital for MSME resilience in the Society 5.0 era.